2001
DOI: 10.1002/ajp.1031
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variability in numbers of live births in wild golden lion tamarins (Leontopithecus rosalia)

Abstract: We examined the effects of several variables on the number of live births in multiparous females in a wild population of golden lion tamarins (Leontopithecus rosalia). Independent variables included the number of infants born to a female the previous breeding season, the number of infants weaned the previous breeding season, the female's age and body mass, the number of adult males and helpers in the group, and the inbreeding coefficient of the offspring. We also tested the hypothesis that trapping and chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 34 publications
4
59
0
Order By: Relevance
“…In common marmosets, for example, there was more within-than betweenfemale variation in the number of ova females ovulated per cycle, and individual females ovulated significantly fewer ova at lower body weights than they did at higher body weights (Tardif and Jaquish, 1997). Similarly, Bales et al (2001) reported that female golden lion tamarins at lower body weights gave birth to smaller litters than females at higher body weights. In a study of the relationship between nursing effort and ovulatory functioning in cotton-top tamarins, Ziegler et al (1990) found that females nursing twin infants exhibited their first postpartum ovulation later in the postpartum period than females nursing singletons and those not nursing infants.…”
Section: Discussionmentioning
confidence: 99%
“…In common marmosets, for example, there was more within-than betweenfemale variation in the number of ova females ovulated per cycle, and individual females ovulated significantly fewer ova at lower body weights than they did at higher body weights (Tardif and Jaquish, 1997). Similarly, Bales et al (2001) reported that female golden lion tamarins at lower body weights gave birth to smaller litters than females at higher body weights. In a study of the relationship between nursing effort and ovulatory functioning in cotton-top tamarins, Ziegler et al (1990) found that females nursing twin infants exhibited their first postpartum ovulation later in the postpartum period than females nursing singletons and those not nursing infants.…”
Section: Discussionmentioning
confidence: 99%
“…We defined the DRY/NR period as the time (during the dry season) when a female was not pregnant or lactating, or when a female was in the first 2 months of pregnancy. In a previous study, Bales et al [2001] found no significant changes in the weight gain of female GLTs during the first 2 months of pregnancy. We assumed that females in the first 2 months of pregnancy would experience minimal costs due to pregnancy (also see Kirkwood and Underwood [1984]).…”
Section: Data Collection and Analysismentioning
confidence: 93%
“…The timing of improvement in a female's condition (e.g., by energy reserves) may play an important role in reproductive success. Results from several studies on wild GLTs suggest that energy intake may influence female fitness, since nonpregnant/early pregnant body weight significantly predicted the number of live-born offspring [Bales et al, 2001], the amount of maternal carrying of offspring [Bales et al, 2002], and female lifetime reproductive success [Bales et al, 2003]. Kirkwood [1983] also found that improved nutrition was related to increased litter sizes in cotton-top tamarins (Saguinus oedipus).…”
Section: Introductionmentioning
confidence: 93%
“…Thus, the care provided by males seems to reduce the metabolic costs of the females, and females reduce their own efforts in the presence of helpers (Fite et al 2005 ;Tardif 1994 ) . In wild golden lion tamarins ( Leontopithecus rosalia ) the number of infants born is positively correlated with the number of helpers in the previous season (Bales et al 2001 ) . It is therefore likely that female future reproductive success is dependent on the amount of help she receives (Price 1992b ) .…”
Section: Platyrrhinesmentioning
confidence: 99%